Assessing the impact of Glutathione on maternal and fetal outcome in pregnancy-induced hypertensive disorders: A case-control study - Arshad, Sonya; Ahmed , Sadaf; Shershah Syed (International Journal of Endorsing Health Science Research, 2020)
Background: Disorders related to hypertension in pregnancy, mainly Pre-eclampsia (PE), and Eclampsia, are the major causes of fetal and maternal morbidity and mortality. The placenta's ischemic blood supply leads to its endothelial dysfunction and reduced glutathione bioavailability involved in its pathogenesis. This study explored maternal serum Glutathione's level and changes and found out its association with fetal growth in pregnancy-induced hypertensive disorders. Methodology: A Multicenter, case-control study was conducted on 240 pregnant females. The investigational group included 180 pregnant females having blood pressure above 140/90 mmHg. The Investigational group was divided into different groups, i.e. Pregnancy-induced hypertension (PIH) group, PE group, and Eclamptic group. 60 normotensive pregnant females were kept in control. The blood samples were obtained to analyze serum Glutathione (GSH) through ELIZA (enzyme-linked immunosorbent assay), while urine samples were obtained for confirmation of the PE status. Fetal well-being and signs of growth restriction were observed using ultrasound. Results: A significant reduction was elucidated in serum glutathione, biparietal diameter, and femur length among all experimental groups p < 0.001. However, no significant difference was observed in the abdominal circumference p=0.122 and Fetal weight p=0.51. A significantly inversely proportional relation was found between serum glutathione and gestational age, fetal weight as well as head circumference in all four groups control (r =-.305 p=0.018) PIH (r =-.618 p =0.000), PE (r=-.707 p=0.000) and Eclampsia (r=-.661 p=0.000). Conclusion: It is to conclude that the fetus's growth was markedly affected by reduced Glutathione in hypertensive disorders of pregnancy with the progression of the disease.